Hypnotherapy and Hypnosis 2020
DOI: 10.5772/intechopen.92755
|View full text |Cite
|
Sign up to set email alerts
|

Inner Navigation and Theta Activity: From Movement to Cognition and Hypnosis According to the Sphere Model of Consciousness

Abstract: EEG theta (4–7 Hz) activity is closely related to hypnosis and hypnotic analgesia, as well as to meditation and absorption. Research further indicates that theta oscillatory power is involved in different cognitive functions, such as spatial navigation, memory, creativity, and divided attention. The current manuscript will provide a synthesis of current knowledge regarding the importance of theta’s different roles in relation to hypnosis and their connections to movement. Indeed, several movement paradigms, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 185 publications
(249 reference statements)
2
32
0
Order By: Relevance
“…These results related to the relationship between reappraisal, mindfulness and neurophysiological changes are further in line with different models of consciousness, such as the Self-awareness, self-regulation, and self-transcendence (S-ART) model ( Vago and David, 2012 ) and the Sphere Model of Consciousness (SMC, Paoletti, 2002 ; Paoletti and Ben-Soussan, 2019 , 2020 ; Paoletti et al, 2020 ). According to the SMC, reappraisal and voluntary movement toward a state of contentless consciousness, also defined as momentary silent consciousness ( Baars, 2013 ; Josipovic, 2019 ) may have a decisive role in the experience ( Paoletti et al, 2020 ; Paoletti and Ben-Soussan, 2020 ), in which focusing one’s attention on silence can be used as a paradigm for facilitating better internal communication through an internal environment intentionally created ( Paoletti and Selvaggio, 2013 ; Paoletti et al, 2017 ; De Fano et al, 2019 ). Consequently, in this study, silence was operationalized as self-reported absence of thoughts and a subjective experience of mental quietness as suggested by various authors ( Rudrauf et al, 2003 ; Hinterberger et al, 2014 ; Josipovic, 2014 , 2019 ; Winter et al, 2019 ; see Table 1 ), thus describing a state in which participants spontaneously experienced and reported a sort of contentless consciousness.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…These results related to the relationship between reappraisal, mindfulness and neurophysiological changes are further in line with different models of consciousness, such as the Self-awareness, self-regulation, and self-transcendence (S-ART) model ( Vago and David, 2012 ) and the Sphere Model of Consciousness (SMC, Paoletti, 2002 ; Paoletti and Ben-Soussan, 2019 , 2020 ; Paoletti et al, 2020 ). According to the SMC, reappraisal and voluntary movement toward a state of contentless consciousness, also defined as momentary silent consciousness ( Baars, 2013 ; Josipovic, 2019 ) may have a decisive role in the experience ( Paoletti et al, 2020 ; Paoletti and Ben-Soussan, 2020 ), in which focusing one’s attention on silence can be used as a paradigm for facilitating better internal communication through an internal environment intentionally created ( Paoletti and Selvaggio, 2013 ; Paoletti et al, 2017 ; De Fano et al, 2019 ). Consequently, in this study, silence was operationalized as self-reported absence of thoughts and a subjective experience of mental quietness as suggested by various authors ( Rudrauf et al, 2003 ; Hinterberger et al, 2014 ; Josipovic, 2014 , 2019 ; Winter et al, 2019 ; see Table 1 ), thus describing a state in which participants spontaneously experienced and reported a sort of contentless consciousness.…”
Section: Introductionsupporting
confidence: 80%
“…It has recently been suggested that through a voluntary act of silence, used as a paradigm similar to sensory deprivation one can intentionally move from the narrative self, to the minimal and eventually overcoming the self ( Paoletti et al, 2020 ; Paoletti and Ben-Soussan, 2020 ). The state of overcoming of the self, which can further be compared with self-transcendence, absorption, and non-dual states ( Josipovic, 2014 ; Vieten et al, 2018 ), is characterized by changes in the perception of time and space shifting gradually toward “timelessness” and “spacelessness” ( Berkovich-Ohana et al, 2013 ; Wittmann, 2015 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Minimal Self has a short temporal extension and is endowed with a sense of action, property, and first person non-conceptual content, while the Narrative Self involves personal identity and continuity through time and includes conceptual content. In our previous papers on the SMC, we specified the addition of a third state, called Overcoming of the Self (see Figure 7 , Paoletti and Ben-Soussan, 2019 ; Paoletti et al, 2020 ), in which all sense of self disappears. In the model, the Minimal Self is depicted as a circle close to the center, contained by a larger circumference that represents the Narrative Self.…”
Section: The Sphere Model Of Consciousnessmentioning
confidence: 99%
“…Thus, in the flat life condition, while we agree with Maslow on many aspects that classifications of motivation should be based also upon conscious goals rather than on drives ( Maslow and Lewis, 1987 ; Paoletti, 2005 ; Paoletti and Ben-Soussan, 2019 ). Thus, the transition to a spherical life, which is accompanied by a change of focus from needs to values ( Paoletti, 2005 ), is further accompanied by an intentional shift away from DMN activity and toward clear goal state, represented by the center of the sphere ( Paoletti, 2002a , b ; Paoletti and Ben-Soussan, 2019 ; Paoletti et al, 2020 ).…”
Section: The Sphere Model Of Consciousnessmentioning
confidence: 99%